1988
DOI: 10.1139/v88-487
|View full text |Cite
|
Sign up to set email alerts
|

LEED and AES studies of chemisorption resulting from low exposures of C2H4, CO, and PH3 to the (0001) surface of zirconium

Abstract: . Can. J. Chem. 66, 3157 (1988). Low-energy electron diffraction (LEED) and Auger electron spectroscopy (AES) have been used to study for the first time the chemisorption systems formed on the (000 1 ) surface of zirconium by exposing to C2H4, CO, and pH3 in the one to ten Langmuir regime. The adsorptions are done at room temperature, but there is subsequent heating to optimize the surface ordering. The main observations are as follows: ( i ) after heating C2H4-covered surfaces to effect hydrogen desorption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…3. LEED intensity analysis has confirmed an ordered ͑1 ϫ 1͒-C structure in a study of C 2 H 4 on Zr͑0001͒, 15 and it is likely that similar structures are present in our work. The electron fluence was 9 ϫ 10 16 electrons/ cm 2 for the latter data set.…”
Section: Resultssupporting
confidence: 84%
“…3. LEED intensity analysis has confirmed an ordered ͑1 ϫ 1͒-C structure in a study of C 2 H 4 on Zr͑0001͒, 15 and it is likely that similar structures are present in our work. The electron fluence was 9 ϫ 10 16 electrons/ cm 2 for the latter data set.…”
Section: Resultssupporting
confidence: 84%
“…The gross Mulliken population of the a 6 S ground state of the Tc atom is computed as 4d 5.015 5s 1.847 , which is in excellent agreement with the anticipated configuration of 4d 5 5s 2 . We have obtained an averaged dissociation limit for the 4 Π, 4 ∆, and 4 Φ states of TcCO since the 4 P, 4 F, and 4 G atomic spectral terms of the technetium atom are quite close to each other, 61 and it is thus difficult to make a definitive determination of the atomic states from the molecular computations.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have dealt with a variety of species of transition metals such as clusters, alloys, and inorganic salts, and especially those pertinent to the second- and third-row transition metals. A primary motivation for such studies is that these species play an important role in the catalytic and chemisorption processes. With these efforts, not only is the determination of the activity for certain chemical reactions available, but also the mechanism of heterogeneous catalysis concerning active sites of transition metals can be investigated. In recent years, synthesis and characterization of organic metal complexes containing carbonyl ligands have received considerable attention. It has been shown that these catalysts exhibit enhanced selectivity and compounds that differ in structure and properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should mention that there is a possibility of formation of a (1 ϫ1)-C structure as was observed for C 2 H 4 /Zr(0001), 16 but we did not perform LEED intensity analysis to verify this. We should mention that there is a possibility of formation of a (1 ϫ1)-C structure as was observed for C 2 H 4 /Zr(0001), 16 but we did not perform LEED intensity analysis to verify this.…”
Section: Leedmentioning
confidence: 94%